Intraocular Lymphoma in Dogs - Findings of Contrast Enhanced Ultrasound and ARFI Elastography - Madruga, Gabriela Morais; Kniphoff da Cruz, Igor Cezar; Carneiro, Rafael Kretzer; Rossi Feliciano, Marcus Antônio; Maronez, Marjury Cristina; Uscategui, Ricardo Ramirez; Morato Abreu, Thais Guimarães; Perlmann, Eduardo (Acta Scientiae Veterinariae, 2022)
Background: Ocular lymphoma can affect the iris, conjunctiva, choroid, and retina and is mostly associated with multicentric disease. Elastography is an ultrasound technique that provides noninvasive, pain-free assessment of tissue stiffness. It has the ability to assess subtle changes throughout the organ as well as focal lesions. Microbubble contrast ultrasound enables the detection of incipient vascular flows, which are difficult to detect using traditional ultrasound methods. This study aimed to describe acoustic radiation force impulse (ARFI) elastography and microbubble contrast ultrasound findings in the eyes of two dogs diagnosed with intraocular T-cell lymphoma. Cases: Case 1. Physical examination revealed an exophytic mass in the left eye. Schirmer test revealed a secretion of 22 mm/min. Negative threat reflex, glare, direct pupillary light reflex, and consensual response were also noted. Biomicroscopy revealed hyperplasia of the third eyelid, overlapping with the affected eye. When the membrane was removed, moderate conjunctival hyperemia, mucoid secretion, and buphthalmia were observed. In addition, significant corneal edema was present, making it impossible to visualize the anterior chamber and perform fundus examination. The intraocular pressure, as measured with a rebound tonometer, was 39 mmHg. B-mode ultrasonography identified amorphous, hyperechoic, and heterogeneous structures throughout the anterior chamber, iris, and ciliary body. The elastogram showed that the mass had greenish tones and intermediate stiffness, and the mean SWV of the ciliary body and iris was 2 m/s. Contrast-enhanced ultrasound (CEUS) revealed vascularization of the neoformation region, with wash-in, peak, and wash-out values of 9.89 s, 24.56 s, and 107.87 s, respectively. Case 2. On physical examination, a change in the shape of the right pupil was observed. Schirmer test revealed a secretion of 20 mm/min, with negative threat, glare, and pupillary reflexes to direct and consensual light. Biomicroscopy revealed neoformation from 7 am to 11 am in the sclera, retina, and choroid complex, concomitant with dyscoria and conjunctival hyperemia. The intraocular pressure, as measured by rebound tonometry, was 33 mmHg. Fundoscopy revealed a mass in the temporal region and focal retinal detachment. No changes were observed in the contralateral eye. B-mode ultrasound revealed an increase in volume in the temporal region of the iris, ciliary body, and choroid with diffuse heterogeneity and partial retinal detachment. Elastographic examination revealed shades of green and yellow compatible with increased tissue stiffness. On quantitative examination, the mean SWVs of the ciliary body and iris were 3.14 m/s. On CEUS, the neoformation region presented wash-in, peak, and wash-out values of 8.67 s, 22.33 s, and 80.20 s. Discussion: B-mode ultrasonography established the tumor extent and evaluated echogenicity, verifying the involved ocular structures. The examination played an important role in the diagnosis as well as clinical management. ARFI elastography can detect small tissue changes, helping to define nodules and masses more reliably, in addition to allowing the verification of tissue stiffness. In both dogs, it was possible to verify that the masses presented greater rigidity than the adjacent tissues both qualitatively and quantitatively. In previous studies, it was found that cutaneous and breast lymphomas in humans were more rigid than adjacent tissues on elastography. This increase in rigidity and heterogeneity observed on elastograms can be explained by the extramedullary interactions of the matrix in T-cell lymphomas. Tumor growth is dependent on the blood supply, which was evaluated using CEUS in these cases. Furthermore, the ciliary body contrast filling times were longer than those described in normal dogs. Keywords: eye, surgery, diagnostic imaging, pain, veterinary ophthalmology, neoplasia. Título: Linfoma intraocular em cães - achados da ultrassonografia contrastada e elastografia ARFI Descritores: olho, cirurgia, diagnóstico por imagem, dor, oftlamologia veterinária, neoplasia.